PENERAPAN METODE PEMBELAJARAN PROYEK FUN COOKING UNTUK MENINGKATKAN KETERAMPILAN MOTORIK HALUS DAN KREATIVITAS (Studi pada anak kelompok anak usia 5-7 tahun Di Posyandu Kelurahan Kebun Roos Kota Bengkulu) - Sabaria Agustina (DIADIK, 2021)
The purpose of this study is to describe the appropriate application of fun cooking project learning methods, so as to improve the fine motor skills of children aged 5-7 years. This research is a type of classroom action research (PTK) with planning, implementation of action (Act), observation, and reflection, in implementation it is carried out for 3 cycles with the subject of children aged 5-7 years at Posyandu Kelurahan. Kebun Roos Bengkulu City, amounting to 10 children, 2 children aged 5 years and 8 children aged 6 years. This data collection technique uses observation and is analyzed using percentages and averages to determine the increase between cycles using the t-test analyst (Test "t"). Based on the research results, it can be concluded that the application of fun cooking project learning can improve fine motor skills and creativity